Drone Adoption Challenges in Malaysia’s Construction Industry - Jamian, Yuhani; Salleh, Shahrun Nazida Binti; Harisman, Salsabila binti (Proceeding Economy of Asia International Conference, 2026)
Introduction/Main Objectives: This study explores the challenges faced by the Malaysian construction industry in adopting drone technology. It is guided by three objectives: 1) to identify technological barriers, 2) to examine organizational and environmental factors, and 3) to analyze relevant demographic correlations. Background Problems: The construction industry recognizes the potential of drone technology, but its widespread adoption is hindered by various significant barriers. Novelty: This study aims to fill a specific research gap by focusing exclusively on the challenges hindering drone adoption within the Malaysian construction industry. Its novelty lies in seeking deep, practical insights directly from on-the-ground industry practitioners (engineers, contractors, supervisors, project managers), whose firsthand perspectives on technical, operational, regulatory, and organizational constraints remain underexplored, especially when compared to studies focusing on general benefits or applications of the technology. Research Methods: The study used a quantitative questionnaire administered via Google Form. Respondents were individuals directly involved in construction (site supervisors, engineers, contractors, technical personnel). Data were analyzed using the Statistical Package for the Social Sciences (SPSS). Finding/Results: Technological Barriers: High cost of equipment (mean=4.00), lack of skilled personnel (mean=4.00), low awareness (mean=4.15), and safety/privacy concerns (mean=4.25) were key challenges. Organizational & Environmental Factors: Key barriers included legal/regulatory restrictions (mean=4.11), lack of technical support (mean=4.22), uncertainty about ROI (mean=4.16), resistance to change (mean=4.11), and weather conditions (mean=4.35). Demographic Correlations: Age was moderately correlated with skill limitations (r=.432), qualification with organisational resistance (r=.542), and experience showed a weak correlation with weather-related challenges (r=.210). Conclusion: Overall, while the industry sees drone technology’s potential, multiple barriers impede adoption. To increase preparedness and confidence, the industry may benefit from more focused training, awareness campaigns, clearer regulatory guidance, and structured cost-benefit analyses.